Silica Particles as Material For Encapsulation and Controlled Release of Drugs and Biologicals - PANDEY SHIVANAND, (International Journal of Pharma and Bio Sciences, 2010)
Bioactive molecules can be easily encapsulated within silica particles by combining sol-gel polymerization with either spray-drying or chemistry. Spray-drying faces challenges, including low yield, surface segregation, and size limitations. In contrast, sol-gel emulsions enable the production of nanoparticles with homogeneous drug distribution, and permit ambient temperature processing. Necessary for handling biologicals. Spherical silica particles are produced using combined sol–gel synthesis and emulsion polymerisation chemistry. Controlled release is achieved by restricting diffusion of encapsulated molecules out of the particles, by tailoring the internal pore structure of the spheres.